Statistical Analysis of Activation Factors for Coffee Husk derived Activated Carbon on Chromium (VI) Adsorption and Carbon yield - Ngo, Thi Thuan; Nguyen, Minh Ngoc; Ly, The Nghia; Tran, Thi Hong Thu; Nguyen, Duy Dat; Chanatip, Samart (ASEAN Journal of Chemical Engineering, 2024)
Coffee husk waste, an abundant waste material in Vietnam, has been utilized to produce activated carbon. However, the single and interactional effects of activation factors for pyrolysis of coffee husk waste have not been studied well. This research proposed a fully statistical strategy including Box-Behnken experimental design, analysis of variance, regression diagnostics, influence degree, optimization and test of good-fitness, analysis of activated carbon’s surface, and aimed to explore activation factors of impregnation ratio (IR) between H3PO4 and the biomass, activation temperature (AT) and time on Cr(VI) adsorption and carbon yield. The antagonistic effects of first-order AT and second-order IR contributed 75.91% of total influence factors and had the greatest impact on carbon yield. In contrast, the second-order AT, IR and the first-order IR, AT, their interaction accounting for 94.77%, had a statistically significant influence on Cr(VI) adsorption capacity. The optimal values of 35% IR, 540oC and 72 minutes could give 72.67±4.13% carbon yield, 104.13±7.64 mg Cr(VI) g-1, and a specific surface area of 1896 m2 g-1 due to an abundance of micropores, mesopores and hydroxyl, carbonyl and carboxylic groups on the biochar’s surface. These findings suggest that the coffee husk waste-derived activated carbon may be a promising adsorbent for Cr(VI) and other small to medium-sized compounds from water, and the second-order polynomial regression model can be used to interpret the pyrolysis conditions to reduce preparation time and overall cost.